FREKUENSI PEMERIKSAAN ANC BERHUBUNGAN DENGAN PREEKLAMPSIA - lina fiitriani; rosdiana rosdiana (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
The gestation period starts from conception until the birth of the fetus. The normal duration of pregnancy is 280 days (40 weeks or 9 months and 7 days) counting from the first day of the last menstruation. Pregnancy is divided into 3, the first trimester starts from conception until 3 months, the second trimester starts from the fourth month to 6 months, the third trimester is from the seventh month to 9 months. Preeclampsia is a disease characterized by hypertension, proteinuria and edema that occurs during pregnancy. or up to 48 hours postpartum. This study aims to determine the frequency of ANC examinations with preeclamptic. The research method used was analytic survey research design with a cross sectional approach. Data collection techniques. Data collection in this study used a questionnaire sheet. The technique used in this study was purposive sampling. The data analysis used was univariate and bivariate analysis and the statistical test used was Chi Square. The significance of the relationship between the two variables is p = 0.000, p = 0.002 <α 0.05, this means that Ha is accepted and Ho is rejected, so there is a relationship between the frequency of ANC examinations and preeclamptic